State Transition Method Analysis for Testing the Interactive Multimedia Applications - Santi Purwanti; Khansa Mufidah Fillah; Jaja jaja; Nita Delima (LPPM Universitas Islam 45 Bekasi, 2024)
Interactive multimedia applications help users to get interactive information, such as an interactive multimedia application, called ‘I Learn to Read’ (ABACA) which can be used by first-grade elementary school students who can interact easily through the ABACA application to learn reading. Yet, to ensure that the multimedia application is interactive according to user needs and guaranteeing the quality of the application, testing needs to be done. Testing is carried out using black box testing which focuses on application functionality, so this research is more focused on black box testing using the State Transition method which consists of four stages, namely state transition testing design, Test Case, Testing, and conclusions from what has been done in the activity ABACA Interactive Multimedia Application testing. Results showed that twenty-three functionalities have been tested and succeeded in displaying transitions by the existing functionalities.